1973
DOI: 10.1002/chin.197331188
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SELECTIVE DEOXYGENATION OF KETONES AND ALDEHYDES INCLUDING HINDERED SYSTEMS WITH SODIUM CYANOBOROHYDRIDE

Abstract: Bei der Reduktion der Tosylhydrazone aliphatischer Aldehyde oder Ketone des Typs (I) bzw. (III) mit Na‐trihydridocyanoborat in einem sauren 1:1‐ Gemisch aus DMF und Sulfolan entstehen ausschließlich die entsprechenden Kohlenwasserstoffe (II) bzw. Cyanester (IV).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
1985
1985

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Analysis of the residue by gas-liquid chromatography showed that the conversion of the acyl chloride to the keto ester (V) ranged from 70% to 95% and it was then further purified by silicic acid column chromatography. The keto ester was deoxygenated (Hutchins et al, 1973) and the ester (VI) also purified by silicic acid column chromatography. The fatty acid (VII) was isolated after deesterification and crystallization .…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of the residue by gas-liquid chromatography showed that the conversion of the acyl chloride to the keto ester (V) ranged from 70% to 95% and it was then further purified by silicic acid column chromatography. The keto ester was deoxygenated (Hutchins et al, 1973) and the ester (VI) also purified by silicic acid column chromatography. The fatty acid (VII) was isolated after deesterification and crystallization .…”
Section: Methodsmentioning
confidence: 99%